Mandatory multidisciplinary management of hepatocellular carcinoma: Need of the hour in a country with high prevalence of hepatitis C virus infection. - Muhammad Rizwan Khan; Saleema Begum (Journal of the Pakistan Medical Association, 2021)
Hepatocellular carcinoma (HCC) is the sixth common cancer diagnosed and fourth leading cause of cancer related deaths worldwide. The incidence of HCC is on rise due to increasing prevalence of chronic hepatitis C virus Infection. Pakistan is ranked second in HCV burdened countries in the world. Management of HCC is complex as it develops on the background of liver cirrhosis; the risk of mortality is contributed both by tumor related factors and liver decompensation. A multidisciplinary tumor board (MDT) is an ideal approach to improve the outcomes of HCC since this ensures assimilation of input from a diverse group of care providers including hepatobiliary and transplant surgeons, gastroenterologists, interventional radiologists, oncologists, and palliative care specialists. MDT provides tailored approach to individual cases in a timely fashion to avoid treatment delays and communication gaps to improve the overall outcomes. Keywords: Hepatocellular carcinoma, multidisciplinary approach, MDT